MAKNA DAN NILAI FILOSOFIS DALAM ARSITEKTUR RUMAH GADANG - Rahmadani, Novia (Studi Budaya Nusantara, 2023)
The rumah gadang as a traditional house of the Minangkabau tribe is very familiar to all Indonesian people. Rumah gadang is also closely related to rangkiang, because rangkiang is an important part of rumah gadang. In the construction of the rumah gadang, what is interesting to study is the architecture of the building wich is designed. All the construction of rumah gadang, both interior and exterior have it’s own value and meaning. To describe that, the writer uses heuristic, observation, interview, descriptive, and literatur research methods. Based on the research that has been carried out using these various methods, it is found the fact that rumah gadang is not only used as aplace to live by the Minangkabau people. Rumah gadang is a source of culture and learning for anak kamanakan in the community of Minangkabau tribe. Therefor, every architecture of rumah gadang is designed in such a way as to imply the philosophical meaning and value. As well as rangkiang what is also part of rumah gadang.